Emerging Role of Microsponges in the Treatment of Psoriasis: A Comprehensive Review - Kokate S.Tanvi,; Dr. Vikrant P. Wankhade,; Dr. Shrikant D. Pande,; Dr. Sandeep C. Atram,; Dr. Nishan N. Bobade,; VikramV.Bhoyar,; Neha S. Ghogare, (Asian Journal of Pharmaceutical Research and Development, 2025)
Psoriasis is a chronic autoimmune inflammatory skin disorder characterised by red, scaly, and itchy plaques, resulting from an accelerated turnover of skin cells due to an overactive immune response. Although various treatment options are available, ranging from topical agents to systemic therapies and biologics, they are often associated with limitations such as poor drug penetration, systemic side effects, and reduced patient adherence. Recent advances in drug delivery, particularly microsponge-based systems, offer a novel approach to overcoming these challenges. Microsponges enable controlled drug release, improved skin retention, and enhanced therapeutic efficacy. This review highlights the potential of microsponge technology in the management of psoriasis and discusses its advantages over conventional formulations.